Exploring the Effectivenss of Critical Thinking Skills in Speaking Skills: Insights from a Vocational School Context - Setianingsih, Tri; Utama, I Made Permadi; Kamarudin, Kamarudin; Sumarni, Baiq (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study explores the impact of the Talking Chips strategy on enhancing critical thinking during English speaking tasks among vocational students. While these students often excel in practical skills, they struggle with critical thinking in English, leading to a skills gap in English as a Foreign Language (EFL) education. Using a quasi-experimental design, two eleventh-grade classes from a Tourism and Travel Business program at vocational schools participated in a pretest-posttest speaking assessment. The experimental group (n = 25) used the Talking Chips strategy, while the control group (n = 25) followed conventional methods. The speaking assessments were evaluated using an analytic rubric, with high inter-rater reliability (0.87). Mann-Whitney U analysis revealed a significant treatment effect (U = [insert value], p = .001, r = [insert effect size]), indicating that the Talking Chips strategy effectively improved students’ analytical reasoning and reflective responses. These findings suggest that cooperative learning strategies, like Talking Chips, can enhance higher-order thinking skills in EFL speaking classrooms. The study concludes that incorporating turn-taking structures in speaking tasks helps foster deeper reasoning and encourages more purposeful argumentation, recommending that teachers use such techniques to promote critical thinking in vocational EFL settings.